KOSMOLOGI DALAM BUDAYA TRADISI TEPUK TEPUNG TAWAR MELAYU PROVINSI RIAU - Selvia Frety Yunia Enjelina; Dian Eka Oktavia; Agusti Efi (Gorga : Jurnal Seni Rupa, 2022)
Unsalted flour also has values that are believed to be a Malay view of life that is closely related to cultural cosmology which contains a symbolic meaning of belief in the power of the universe or a thank you to God the Creator of Nature.. In this study, a cosmology of the traditional Malay patty flour culture was carried out in Riau Province. The purpose of this study is to increase the reader's understanding of how cosmology is in research, so that by studying art cosmology it will make it easier to give appreciation to an art and can make art and artists better in the future. With the cosmology in the culture of the Malay fresh flour pat tradition, it can be known about the function of cosmology in the life of the Malay community as well as the use of the Malay fresh flour pat tradition. The research method used in this study is descriptive qualitative, where a description of the traditional Malay culture of patting flour in Riau Province is carried out and the sampling technique used is purposive sampling. The main discussion in this study is a description of the traditional Malay patty flour culture, so that it succeeds in describing the meaning and function of the Malay traditional flour patting culture. Therefore, it is necessary to understand well how the meaning and function of cosmology in a culture, one of which is the Malay tradition of patting fresh flour, can thus preserve a culture and make culture or art better.Keywords: appreciation art, meaning, function cosmology. AbstrakTepung tawar juga memiliki nilai-nilai yang dipercaya sebagai pandangan hidup bermasyarakat Melayu yang erat kaitannya dengan kosmologi budaya yang mengandung makna simbolik kepercayaan atas kekuatan alam semesta atau ucapan terima kasih kepada Tuhan pencipta alam. Pada penelitian ini dilakukan suatu kosmologi dalam budaya tradisi tepuk tepung tawar Melayu di Provinsi Riau. Tujuan dari penelitian ini yaitu untuk meningkatkan pemahaman pembaca terkait bagaimana kosmologi dalam penelitian, sehingga dengan mempelajari kosmologi kesenian maka akan mempermudah dalam memberikan penghargaan terhadap suatu seni serta dapat menjadikan kesenian maupun seniman menjadi lebih baik untuk ke depannya. Dengan kosmologi dalam budaya tradisi tepuk tepung tawar Melayu dapat diketahui mengenai fungsi kosmologi dalam kehidupan masyarakat melayu serta penggunaan dari tradisi tepuk tepung tawar Melayu. Metode penelitian yang dipakai pada penelitian ini yaitu penelitian deskriptif kualitatif, dengan dilakukan pendeskripsian mengenai budaya tradisi tepuk tepung tawar Melayu di Provinsi Riau dan teknik sampling yang dipakai yaitu purposive sampling. Pembahasan inti dalam penelitian ini adalah pendeskripsian mengenai budaya tradisi tepuk tepung tawar Melayu, sehingga berhasil menguraikan bagaimana makna dan fungsi dari budaya tradisi tepuk tepung tawar Melayu. Oleh karena itu perlu dipahami dengan baik bagaimana makna dan fungsi dari kosmologi dalam suatu budaya salah satunya tradisi tepuk tepung tawar Melayu, dengan demikian dapat melestarikan suatu kebudayaan dan menjadikan kebudayaan atau kesenian menjadi lebih baik.Kata Kunci: apresiasi seni, makna, fungsi kosmologi. Authors:Selvia Frety Yunia Enjelina : Universitas Negeri PadangDian Eka Oktavia : Universitas Negeri PadangAgusti Efi : Universitas Negeri Padang References:Enjelina, F. S. Y. (2021). “Tradisi Tepuk Tepung Tawar Melayu”. Hasil Dokumentasi Pribadi: 10 September 2021. Lembaga Adat Melayu Riau.Batubara, S. M. (2017). Kearifan lokal dalam budaya daerah kalimantan barat (etnis melayu dan dayak). Jurnal Penelitian IPTEKS, 2(1). 91-104.Batubara, T., Badrun, B., & Muhajir, A. (2022). Tradisi Tepung Tawar: Integrasi Agama dan Kebudayaan pada Masyarakat Melayu di Sumatera Utara. Local History & Heritage, 2(1), 10-16.Ernawati, E. (2019). Kosmologi sebagai Pijakan Kreasi dalam Berkarya Seni (Cosmology as the Foundation of Creation in Artwork). INVENSI (Jurnal Penciptaan Dan Pengkajian Seni), 4(2), 113-129.Subiyantoro, S. (2009). Patung Loro Blonyo dalam Kosmologi Jawa. Humaniora, 21(2), 162-173.